Perceived Learning and Students' Satisfaction as The Real-Event Organizer of the International Hospitality Entrepreneurship and Innovation Conference (InHEIC) - Sihombing, Irene Hanna H.; Suastini, Ni Made (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
The purpose of this research is to explore the relationship between perceived learning outcomes and student learning satisfaction in organizing international conferences. Specifically, this research aims to answer how organizing international conferences as a final project affects students' learning satisfaction, perceived learning outcomes, and the relationship between perceived learning outcomes and students' learning satisfaction in organizing international conferences as a final project. Data collection using a questionnaire, in the form of a Google Form. A questionnaire was given to all 8th semester students of the 2017, 2018 and 2019 Hotel Management study program with a total of 86 students. The results show that student learning satisfaction and perceived learning outcomes are in the very good category. There is a strong correlation for perceived learning and satisfaction at the International Hospitality Entrepreneurship and Innovation Conference (InHEIC) event.